Respon Masyarakat Islam Terhadap Eksistensi Sunda Wiwitan di Kampung Adat Cireundeu, Cimahi - Arif Sutrisna; Tarpin Tarpin (Priangan: Journal of Islamic Sundanese Culture, 2023)
AbstractThe purpose of this research is to analyze and at the same time know the response of the Islamic community to the existence of Sunda Wiwitan in the Cireundeu Traditional Village. Therefore, the existence of the Sundanese Religion or commonly referred to as Sunda Wiwitan is still maintained in its authenticity in the Cireundeu Traditional Village, Cimahi. The method used in this research is a qualitative historical research method. Sunda Wiwitan is an ancestral religion that adheres to animism-dynamism or local beliefs which are still preserved and preserved today. Not all of the people who live in the Cireunde Traditional Village, Cimahi follow these local beliefs, there are even people who are diverse in Islam, but the people there have never had any conflict, and they can even respect each other so that they can make the Cireunde Traditional Village a village that is not only only exist in their local beliefs but on the other hand the culture that supports this diversity makes the Cireunde Traditional Village still maintain the culture of the Archipelago. Keywords: Traditional Village, Cireunde, the Archipelago. AbstrakTujuan penelitian ini untuk menganalisis sekaligus megetahui respon masyarakat islam terhadap eksistensi Sunda Wiwitan di Kampung Adat Cireundeu. Maka dari itu eksisnya Agama Sunda atau biasa disebut sebagai Sunda Wiwitan masih di pertahankan keasliannya di Kampung Adat Cireundeu,Cimahi. Metode yang dipakai dalam penelitian kali ini adalah metode penelitian sejarah yang bersifat kualitafif. Sunda  Wiwitan Adalah agama nenek moyang yang menganut animisme-dinamisme atau kepercayaan lokal yang sampai saat ini masih di jaga dan di lestarikan. Masyarakat  yang berada di lingkungan Kampung Adat Cireunde, Cimahi tidak semuanya ikut kedalam kepercayaan lokal tesebut bahkan ada masyarakat yang beragam Islam, tapi masyurakat disan sepenuhnya tidak pernah ada konflik bahkan merekan bisa mengahargai satu sama lain sehingga bisa menjadikan Kampung Adat Cireunde menjadi Kampung yang tidak hanya eksis                                         dalam kepercayaan lokalnya saja tapi di sisi lain budaya yang menopang keberagaman tersebut menjadikan Kampung Adat Cireunde tetap mempertahankan kebudayaan Nusantara.  Kata kunci: Kampung Adat, Cireunde , kebudayaan Nusantara.